Comparison Of Eosinophil Counts In Copd Group B And Group E Patients - Anita Fitriani Siregar; Pandiaman Pandia (Riviera Publishing, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive lung disease associated with chronic inflammation due to exposure to toxins and one of inflammation biomarkers is eosinophil counts which found to be increased in COPD cases and also associated with patient outcome. Aims : This research aims to analyze the differences of eosinophil counts in COPD patients either Group B or Group E at Prof. Dr. Chairuddin Panusunan Lubis Hospital, North Sumatra. Material and Methods: This is an observational analytical study with case-control design. Data were obtained retrospectively from medical records, with the main variable is eosinophil counts obtained from routine blood tests. Additional variables included gender, age, smoking history, level of shortness of breath (mMRC), history of exacerbations, body mass index (BMI), and education level. Bivariate analysis used the T-independent test for normally distributed data and Mann Whitney test for non-normally distributed data, p-value <0.05 indicates statistically significant results. Results: Most of COPD patient either in Group B or Group D was a heavy smoker with obesity type 2 and shortness of breath which indicated by a high mMRC score. Mean eosinophils values in COPD Group B patients was 248,677±294,739 while in COPD Group E patients it was 151,290±190,416. Analysis with T- Independent -test to compare eosinophil counts between Group B and Group E showed a statistically significant difference, with a p-value of 0.000 (p <0.05). Conclusion : COPD group B patients have a higher number of eosinophils than COPD group E which indicated a significant inflammatory process in group B, while more stable diseases in group E.